Stability and Solvability of Discrete Generalized Proportional Caputo Fractional Neural Network Models - Bohner, Martin; Gupta, Rajrani (Sarajevo Journal of Mathematics, 2026)
This study examines the stability in variable-order fractional discrete neural networks modeled via the generalized proportional Caputo fractional difference operator. By employing the Krasnoselskii fixed-point theorem, we establish solution existence under Lipschitz continuity, and we prove Ulam–Hyers stability. Numerical simulations validate that balancing network parameters and fractional orders ensure robustness.